Writing desire : sixty years of gay autobiography - Cohler, Bertram J. (Wisconsin studies in autobiography., 2007)
Exploring nearly sixty years of memoir and autobiography, Writing Desire examines the changing identity of gay men writing within a historical context. Distinguished scholar and psychoanalyst Bertram J. Cohler has carefully selected a diverse group of ten men, including historians, activists, journalists, poets, performance artists, and bloggers, whose life writing evokes the evolution of gay life in twentieth-century America.